Answer:
x=0
Explanation:
Simplifying
2x + -6 = 4x + -6
Reorder the terms:
-6 + 2x = 4x + -6
Reorder the terms:
-6 + 2x = -6 + 4x
Add '6' to each side of the equation.
-6 + 6 + 2x = -6 + 6 + 4x
Combine like terms: -6 + 6 = 0
0 + 2x = -6 + 6 + 4x
2x = -6 + 6 + 4x
Combine like terms: -6 + 6 = 0
2x = 0 + 4x
2x = 4x
Solving
2x = 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
2x + -4x = 4x + -4x
Combine like terms: 2x + -4x = -2x
-2x = 4x + -4x
Combine like terms: 4x + -4x = 0
-2x = 0
Divide each side by '-2'.
x = 0
Simplifying
x = 0